Matched control study of visual outcomes after arteriovenous sheathotomy for branch retinal vein occlusion - Yamane S (Dove Medical Press, 2014)
Shin Yamane,1 Motohiro Kamei,2 Susumu Sakimoto,2 Maiko Inoue,1 Akira Arakawa,1 Mihoko Suzuki,2 Nagakazu Matsumura,2 Kazuaki Kadonosono11Department of Ophthalmology, Yokohama City University Medical Center, Yokohama, 2Department of Ophthalmology, Osaka University Graduate School of Medicine, Osaka, JapanBackground: The purpose of this study was to evaluate visual outcomes of arteriovenous sheathotomy for macular edema due to branch retinal vein occlusion (BRVO).Methods: The medical records of 45 eyes from 45 patients who had undergone vitrectomy surgery with arteriovenous sheathotomy for BRVO were studied. Forty-five eyes of 45 patients with a BRVO but without intervention were studied as the control group. The best-corrected visual acuity and central macular thickness were compared between the two groups at baseline and at 1, 3, 6, and 12 months postoperatively.Results: Improvement of best-corrected visual acuity was 0.42 logarithm of the minimum angle of resolution (logMAR) units in the sheathotomy group and 0.22 logMAR units in the control group (P=0.007). The mean postoperative central macular thickness was significantly thinner in the sheathotomy group at 1 month (P=0.01), but not at 3, 6, and 12 months (P=0.75, P=0.81, and P=0.46, respectively). Improvement of best-corrected visual acuity at 12 months was significantly correlated with baseline best-corrected visual acuity, age, duration of symptoms, and sheathotomy (P<0.05).Conclusion: Arteriovenous sheathotomy for BRVO improves best-corrected visual acuity significantly more than the natural course of the BRVO disease process.Keywords: branch retinal vein occlusion, sheathotomy, macular edema, vitrectomy, observation